The effect of performance appraisal system towards employee performance, employee motivation and employee satisfaction - Ismail, Fadillah; Salahudin, Shahrul Nizam; Jaes, Lutfan; Yusoff, Mohd Zarir; Chai, Jaan Xin; Alhosani, Adnan Ali Hassan Humaid (2022)
Human resources management (HRM) practices such as performance appraisal system (PAS) will affect the employees in a positive and negative ways from the aspects of performance, motivation and satisfaction. Thus, the purpose of this research is to measure the level of employee performance, motivation and satisfaction and to determine the effect of performance appraisal system towards employee performance, motivation and satisfaction at ABC Sdn. Bhd. that located at Selangor. Quantitative research approach along with cross-sectional research design has been used to collect data from 177 employees in the target population through a self-administered and online platform. The return rate of this research from the respondents was 98.30%. The results of the current study provide empirical evidence on key issues related to PAS of employees at ABC Sdn. Bhd. Main finding of this research showed that the employee performance, motivation and satisfaction were in a high and moderate level and there is positive relationship between the performance appraisal system and employee performance (r=0.719), motivation (r=0.836) as well as satisfaction (r=683). This study also proved that performance appraisal system has significant effect towards employee performance (r2=0.508), motivation (r2=0.663) and satisfaction (r2=0.522). This research gives clear directions to stakeholders on the existing performance appraisal system for improvement of the employee performance, motivation and satisfaction at LSF or other private sectors.